Anisotropic composite model for layered rock mass based on characteristics of soft interfaces. (April 2015) - Wu, B.; Jia, S. P.; Luo, J. Z.
Abstract : Based on the Drucker–Prager criterion, an anisotropic composite model of layered rock mass is proposed with the physico-mechanical characteristics of soft interface and rock matrix, and it can be used to describe the anisotropic characteristics of rock strength and deformation, as well as progressive failure or sliding characteristics. Then, the proposed model has been successfully established and embedded on the basis of the developing platform of ABAQUS and MATLAB, realising nonlinear numerical calculation. Through a typical example, the proposed model is verified. Finally, the proposed model is used to simulate a tunnel construction project, and the results show that this model can better explain the deformation and failure phenomenon of layered rock mass, and they are in accordance with engineering practice.